Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Disiplin Kerja Karyawan PT Semarang Power Mandiri - Primadhani, Whindy Nadilla; Pitoyo, Djoko (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2024)
PT Semarang Power Mandiri is a company engaged in the maintenance of CCTV (Closed Circuit Television), AC (Air Conditioner) and outsourcing services. PT Semarang Power Mandiri has non-shift employee working hours, namely 07.00-16.00 with a working time of 8 (eight) hours. There are still many employees who come late, this shows the level of discipline that is still lacking. This study aims to determine the factors that influence the work discipline of employees at PT Semarang Power Mandiri, namely leadership and organizational culture factors. Data analysis using Multiple Linear Regression. The population in this study were non-shift employees of PT Semarang Power Mandiri, totaling 68 people, with a total sample of 41 people. The results of the study show that leadership and organizational culture have a positive influence simultaneously on employee work discipline at PT Semarang Power Mandiri, which is equal to 74.5%.